Analisis pengaruh kepemilikan manajerial, kepemilikan institusional, kebijakan dividen, profitabilitas, ukuran perusahaan dan struktur asset terhadap kebijakan hutang pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia periode 2010-2012 - Dewi Purwasih; Restu Agusti; Al-azhar L (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this study is to analyze the factors that influence debt policy. The factors tested in this study is the managerial ownership, institutional ownership, dividend policy, profitability, firm size and asset structure of the debt policy on companies listed in Indonesia Stock Exchange. Debt policy as a dependent variable in this study is measured by Debt Ratio.Research using purposive sampling method for taking samples. Based on the defined criteria, the sample obtained 30 companies of Manufacturing Firms listed in Indonesia Stock Exchange during 2010 to 2012, therefore the number of data samples in this study is 90 samples.The results of research that profitability and firm size significantly influence debt policy at a significance level (alpha) 5 %. While the variables of managerial ownership, institutional ownership, dividend policy and asset structure do not significantly influence debt policy. The influence of independent variables on the dependent variable (debt ratio) which can be described by the equation by 10,3%. While 89,7% influenced by another factors not included on the regression model.KEYWORDS : Debt Policy, Managerial Ownership, Institutional Ownership, Dividend Policy, Profitability, Firm Size and Asset Structure